Characterization of the flamenco region of the Drosophila melanogaster genome. - Robert, V (2001)
The flamenco gene, located at 20A1-3 in the beta-heterochromatin of the Drosophila X chromosome, is a major regulator of the gypsy/mdg4 endogenous retrovirus. As a first step to characterize this gene, approximately 100 kb of genomic DNA flanking a P-element-induced mutation of flamenco was isolated. This DNA is located in a sequencing gap of the Celera Genomics project, i.e., one of those parts of the genome in which the "shotgun" sequence could not be assembled, probably because it contains long stretches of repetitive DNA, especially on the proximal side of the P insertion point. Deficiency mapping indicated that sequences required for the normal flamenco function are located >130 kb proximal to the insertion site. The distal part of the cloned DNA does, nevertheless, contain several unique sequences, including at least four different transcription units. Dip1, the closest one to the P-element insertion point, might be a good candidate for a gypsy regulator, since it putatively encodes a nuclear protein containing two double-stranded RNA-binding domains. However, transgenes containing dip1 genomic DNA were not able to rescue flamenco mutant flies. The possible nature of the missing flamenco sequences is discussed.